2016
DOI: 10.3892/mmr.2016.4910
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the malaria parasite protein PfTip, a novel invasion-related protein

Abstract: Malaria is one of the most common infective diseases in the world. Invasion of host erythrocytes by the malaria parasite is crucial for pathogen survival and pathogenesis. Various proteins mediate parasite invasion and identification of novel invasion-related proteins may aid in elucidating the underlying molecular mechanism and new intervention strategies for malaria control. This study characterized the PfTip protein, a homolog of the human T‑cell immunomodulatory protein, and examined its function in preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…TIPHs and ITGA homologs are widely present in eukaryotes [ 24 , 25 , 26 ], while VCBS repeat is present at high copy numbers in some species of the bacterial Vibrio, Colwellia, Bradyrhizobium and Shewanella (InterPro domain IPR010221) [ 27 ]. TIPHs, ITGA and VBSC repeat are known for their adhesion property involved in cell-to-cell interactions and have been identified in other apicomplexan parasites (e.g., Toxoplasma and Plasmodium ) for their potential involvement in the attachment and invasion of parasites into host cells [ 25 , 26 , 28 , 29 ]. In the present study, we experimentally confirmed the binding affinity of the N-terminal half of the CpTIPH to host cells, and observed low nanomolar K d binding affinity, suggesting that CpTIPH is an excellent cell surface binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…TIPHs and ITGA homologs are widely present in eukaryotes [ 24 , 25 , 26 ], while VCBS repeat is present at high copy numbers in some species of the bacterial Vibrio, Colwellia, Bradyrhizobium and Shewanella (InterPro domain IPR010221) [ 27 ]. TIPHs, ITGA and VBSC repeat are known for their adhesion property involved in cell-to-cell interactions and have been identified in other apicomplexan parasites (e.g., Toxoplasma and Plasmodium ) for their potential involvement in the attachment and invasion of parasites into host cells [ 25 , 26 , 28 , 29 ]. In the present study, we experimentally confirmed the binding affinity of the N-terminal half of the CpTIPH to host cells, and observed low nanomolar K d binding affinity, suggesting that CpTIPH is an excellent cell surface binding protein.…”
Section: Discussionmentioning
confidence: 99%